2019
DOI: 10.1016/j.resuscitation.2019.02.035
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the effect of dispatcher-assisted CPR on outcomes from sudden cardiac arrest in adults and children

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 48 publications
(107 reference statements)
2
61
0
6
Order By: Relevance
“…ILCOR commissioned an SR to address the effect of DA-CPR on outcomes for patients in out-of-hospital cardiac arrest (OHCA). 3 A draft CoSTR was posted for public comment on the ILCOR website 15 ; the draft was viewed 1516 times during the public comment period. The task force reviewed the 1 comment posted during this public commenting period.…”
Section: Basic Life Supportmentioning
confidence: 99%
See 4 more Smart Citations
“…ILCOR commissioned an SR to address the effect of DA-CPR on outcomes for patients in out-of-hospital cardiac arrest (OHCA). 3 A draft CoSTR was posted for public comment on the ILCOR website 15 ; the draft was viewed 1516 times during the public comment period. The task force reviewed the 1 comment posted during this public commenting period.…”
Section: Basic Life Supportmentioning
confidence: 99%
“…The similarity in outcomes when CPR is initiated spontaneously without the need for dispatch assistance (perhaps performed by a more skilled or trained bystander) and when DA-CPR is performed (perhaps with a less skilled or untrained bystander) exemplifies the potential positive impact of such point-ofcare instruction. At a minimum, DA-CPR increases the likelihood that bystander CPR will be performed, 3 itself an important predictor of favorable outcome from OHCA. 47 The SR also found that DA-CPR favored not only bystander CPR but also time to CPR, ROSC, and initial shockable rhythm.…”
Section: Justification and Evidence To Decision Framework Highlightsmentioning
confidence: 99%
See 3 more Smart Citations